DRP3 and ELM1 are required for mitochondrial fission in the liverwort Marchantia polymorpha - Nagisa Nagaoka (Nature Portfolio, 2017)
Abstract Mitochondria increase in number by the fission of existing mitochondria. Mitochondrial fission is needed to provide mitochondria to daughter cells during cell division. In Arabidopsis thaliana, four kinds of genes have been reported to be involved in mitochondrial fission. Two of them, DRP3 (dynamin-related protein3) and FIS1 (FISSION1), are well conserved in eukaryotes. The other two are plant-specific ELM1 (elongated mitochondria1) and PMD (peroxisomal and mitochondrial division). To better understand the commonality and diversity of mitochondrial fission factors in land plants, we examined mitochondrial fission-related genes in a liverwort, Marchantia polymorpha. As a bryophyte, M. polymorpha has features distinct from those of the other land plant lineages. We found that M. polymorpha has single copies of homologues for DRP3, FIS1 and ELM1, but does not appear to have a homologue of PMD. Citrine-fusion proteins with MpDRP3, MpFIS1 and MpELM1 were localized to mitochondria in M. polymorpha. MpDRP3- and MpELM1-defective mutants grew slowly and had networked mitochondria, indicating that mitochondrial fission was blocked in the mutants, as expected. However, knockout of MpFIS1 did not affect growth or mitochondrial morphology. These results suggest that MpDRP3 and MpELM1 but neither MpFIS1 nor PMD are needed for mitochondrial fission in M. polymorpha.